(untitled) (Nonconventional Technologies Review, 2024)
The International Conference of Nonconventional Technologies is the most representative Romanian conference dedicated to nonconventional machining technologies and has a tradition of 51 years old in the scientific world. The 2024 year, 23th edition subscribes to the current context in which nanotechnologies as part of nonconventional machining are the future of the planet, and their importance in the economic development of every region is heavily considered. The event is occasioned by the 70th anniversary of Manufacturing Engineering Department (TCM) from the Faculty of Industrial Engineering and Robotics, National University of Science and Technology POLITEHNICA Bucharest.